1-Pyrrolyl-10-decylammoniumphosphonate monolayer: a molecular nanolink between electropolymerized pyrrole films and nickel or titanium surfaces. (10th July 2015) - Jacques, A.; Barthélémy, B.; Delhalle, J.; Mekhalif, Z.
Graphical abstract: Schematic representation of the work methodology (SAM formation and/or electropolymerization of pyrrole). Abstract: Among the various conducting polymers, polypyrrole (PPy) is one of the most studied systems for electrochemical synthesis on active metals due to its interesting properties (low oxidation potential, corrosion resistance and biocompatibility). The present work investigates the electropolymerization of pyrrole (Py) on Ni and Ti substrates modified with 1-pyrrolyl-10-decylammoniumphosphonate (PyDPA) (graphical abstract). The self-assembled monolayers (SAMs) of PyDPA improve the corrosion resistance of Ni and Ti and the adherence of the PPy films. The characteristics of the electropolymerized Py films on the PyDPA SAMs appear to be significantly dependent on the nature of the underlying modified substrate (Ni or Ti). A faster electropolymerization process with longer and more stable polymer chains is obtained in the case of Ni, while a slower electropolymerization process due to an incomplete nucleation step (after 30 min in potentiostatic conditions) is observed for Ti modified by PyDPA.